Evaluation of anti-plaque and anti-inflammatory efficacies of mouth rinse containing green tea and Salvadora Persica L. in the management of dental biofilm-induced gingivitis - Saeed Salman, Aliaa; Abdul Azeez Ahmed, Maha ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The plaque accumulation is the main cause of gingivitis, Biofilm-induced gingivitis can be effectively treated by a combination of measures that include motivation and oral hygiene instruction (OHI), professional mechanical plaque elimination, in addition to the supplementary use of antibacterial and anti-inflammatory oral hygiene agents. Therapeutic mouthwash can improve oral hygiene, e.g., by reducing dental biofilm and gingivitis. Chlorhexidine (CHX) is the main mouthwash employed for chemical plaque reduction. CHX is associated with certain adverse effects, including extrinsic staining of teeth. The unwanted effects necessitate the development of new mouthwashes that are equally effective yet devoid of these issues. A mouth rinse containing Green Tea (GT) and Salvadora Persica L. (SP) was investigated for its use in the treatment of gingivitis, and they found that it is effective in reducing gingivitis.